THE EFFECT OF WORK DISCIPLINE, INTERNAL ENVIRONMENT AND EMPLOYEE SATISFACTION ON EMPLOYEE PRODUCTIVITY CV. LANGGENG PROPERTINDO - Diva Salsabila Rahmadani; Iskandar Ali Alam (Transpublika Publisher, 2024)
This study aims to conduct a more in-depth evaluation of the impact of Work Discipline, Internal Environment, and Employee Satisfaction on Work Productivity in the organizational environment of CV. Langgeng Propertindo. The population identified as the object of research is all employees of CV. Langgeng Propertindo, which involved 40 people in this analysis. The method of analysis used is multiple linear regression, a statistical analysis technique that makes it possible to understand the complex interrelationships between independent variables and dependent variables. The results of this study revealed interesting findings: First, work discipline did not have a significant effect on employee productivity. Second, the internal environment did not show a significant impact on work productivity. However, interestingly, Employee Satisfaction positively and significantly affects work productivity. This finding provides a deeper understanding of the factors that really affect employee performance at CV. Langgeng Propertindo. This research also highlights that work productivity is not only influenced by one factor, but simultaneously by work discipline, internal environment, and employee satisfaction.